2016
DOI: 10.1080/10837450.2016.1199566
|View full text |Cite
|
Sign up to set email alerts
|

An integrated, quality by design (QbD) approach for design, development and optimization of orally disintegrating tablet formulation of carbamazepine

Abstract: The objective of the present study was to design and develop a formulation for orally disintegrating tablets (ODTs) of carbamazepine using quality by design principles. The target product profile (TPP) and quality target product profile (QTPP) of ODTs were identified. Risk assessment was carried out by leveraging prior knowledge and experience to define the criticality of factors based on their impact by Ishikawa fishbone diagram and preliminary hazard analysis tool. Box-Behnken response surface methodology wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…The CPPs underlying the identified CQAs were further analysed by FMEA. In a work presented by Mishra et al (25) RA based on Ishikawa diagram and PHA was used in order to elucidate factors that influence the defined QTPPs in the case of carbamazepine containing orally disintegrating tablets. Zhang et al (26) applied the Ishikawa diagram as an appropriate quality RA tool for the identification of CQAs in the case of a stability-indicating RP-HPLC method for a forced degradation study of cloxacillin.…”
Section: Risk Assessment Methods For Control Strategy Of Pharmaceutical Processesmentioning
confidence: 99%
“…The CPPs underlying the identified CQAs were further analysed by FMEA. In a work presented by Mishra et al (25) RA based on Ishikawa diagram and PHA was used in order to elucidate factors that influence the defined QTPPs in the case of carbamazepine containing orally disintegrating tablets. Zhang et al (26) applied the Ishikawa diagram as an appropriate quality RA tool for the identification of CQAs in the case of a stability-indicating RP-HPLC method for a forced degradation study of cloxacillin.…”
Section: Risk Assessment Methods For Control Strategy Of Pharmaceutical Processesmentioning
confidence: 99%
“…Next, 50 mL of the filtrate was obtained and titrated with hydrochloric acid with 0.1 M sodium hydroxide solution (pH measurement method) with an endpoint of pH 3.5. A blank was also generated in the same manner and the acidneutralizing capacity was calculated as follows: The quality target product profile (QTPP) is the basis for formulation and production process design in drug development [36][37][38]. Parameters include clinical use, route of administration, formulation, delivery system, content, container and packaging, API release or delivery, characteristics affecting pharmacokinetic properties, sterility, purity, stability, and dissolution ( Table 1).…”
Section: Analysis Of Acid-neutralizing Capacity Based Sodium Bicarbonmentioning
confidence: 99%
“…A. Amelian et al [16]formulated orally disintegrating loratadine tablet manufactured with co-processed mixture (Kollidon CL-F, CL-SF) by direct compression method, prepared tablets was of appropriate mechanical properties, disintegration time below 30 seconds was observed in formulation with crospovidone as disintegrant. M. Saurabh et al [17]studied an integrated, quality by design (QbD) approach for design, development, and optimization of an orally disintegrating tablet formulation of carbamazepine; he found that kollidon CL-SF concentration was optimum to prepare orally disintegrating tablet formulation of carbamazepine of desired attributes; thus it was found to be best sublimating agent and disintegrant, respectively. R. Sheshala et al [18]formulated orally disintegrating tablets of sumatriptan succinate, the formulation containing kollidon CL-SF disintegrated in the oral cavity within 41 s and released more than 90% of the drug within15 minute.…”
Section: Kollidon® Cl-f Cl-sfmentioning
confidence: 99%